The Faktor-Faktor Yang Berhubungan Dengan Kejadian Preeklamsia Pada Ibu Hamil : A Literature Review - Mauliddya Hanifa; Desy Dwi Cahyani (An Idea Nursing Journal, 2023)
Preeclampsia is a major source of morbidity and mortality in the world and is a complication of pregnancy. In Indonesia, the incidence of preeclampsia/eclampsia is 31.15% in all pregnant women. Preeclampsia often occurs in primigravida, pregnant women who are too young or too old, women with obesity, and a history of hypertension in pregnant women. The purpose of this study was to determine the factors associated with the incidence of preeclampsia in pregnant women and to determine the dominant factors that cause preeclampsia in pregnant women. Literature review research method with traditional literature review design. The results of the literature search there were 13 journals analyzed entirely about the factors associated with the incidence of preeclampsia in pregnant women. Researchers conducted an analysis of 13 journals consisting of 10 national journals and 3 international journals obtained from the Google Scholar and Pubmed databases. The researcher determined the inclusion and exclusion criteria according to the research objectives. The conclusion in this study was that from 13 journals, it was found that the factors causing preeclampsia were parity factors, age factors, history of hypertension factors, nutritional status factors based on BMI and ANC visits. The dominant factor found is the age factor where the entire journal discusses the age factor as the cause of preeclampsia in pregnant women.